Strain-tunable lattice thermal conductivity of the Janus PtSTe monolayer. (27th October 2021) - Pan, Lijun; Carrete, Jesús; Wang, Zhao
Abstract: Using first-principles calculations and Boltzmann transport theory, we study the effect of biaxial tensile strain on phonon transport in a Janus PtSTe monolayer. The band gap between the optical and acoustic phonon branches shrinks with increasing strain, resulting in a highly nonlinear monotonic decrease in the lattice thermal conductivity. That reduction reaches close to an order of magnitude when the gap disappears completely under high strains (>8%). This behavior is attributed to a strong enhancement of the anharmonic scattering of acoustic phonons due to the band overlap. Our findings underscore the potential of strain engineering as a class of methods to tune the thermal transport properties of two-dimensional (2D) Janus nanomaterials.